Minimum-area ellipse bounding an isovist: towards a 2D GIS-based efficient implementation. Issue 5 (4th May 2021) - Leduc, Thomas; Leduc, Michel
ABSTRACT: In geographic information science and technology, various methods and studies exist to characterize the linearity, rectangularity, convexity, circularity or compactness, sinuosity or tortuosity of a given spatial shape. Although there is much work on ellipticity in image processing, we do not address, in geomatics, the issue of matching to a reference elliptical shape. Regarding this issue, this article is a contribution to the qualification of urban open spaces. It provides an operating algorithm for determining a minimum-area bounding ellipse for any given polygonal shape. It also proposes an implementation of this algorithm in the context of a Geographic Information System and a Jupyter Notebook. As an application, it focuses on two real urban configurations on fields of about 300 isovists. The results from the application of this approach in two urban areas in France show that the ellipse is a better minimum bounding geometry than are circle or rectangles, at least for the half-dozen descriptors studied. The improvement relatively to the minimum bounding rectangle is particularly significant in terms of correlation concerning the orientation (+20%) and drift (+10%).